Adsorpsi Logam (Pb) dengan Menggunakan Biji Kelor sebagai Adsorben - Muh. Agus Sharah (JURNAL KRIDATAMA SAINS DAN TEKNOLOGI, 2023)
Lead or in everyday life is better known as lead, in scientific language it is called lead, and this metal is symbolized by Pb. This metal is included in group IV-A metals on the periodic table of chemical elements. It has an atomic number (NA) of 82 and an atomic weight (BA) of 207.2 (Palar, 2008). Lead in air is in the form of Pb (OH)2. Most of the lead metal on earth enters natural water systems and accumulates, which can eventually enter the bodies of animals and humans, which can cause children's intelligence to decrease, stunted body growth, and even cause paralysis. other symptoms such as poisoning, nausea, anemia, and stomach ache. One absorbent material that can be used to adsorb heavy metals such as lead is moringa oleifera seeds. This research uses a method to obtain the desired quantitative and qualitative data regarding PB metal content before adsorption and after adsorption, adsorption time, and quality of Moringa seeds as an adsorbent, then analyzed proximally. The results of the research showed that the Pb concentration in Tallo River water was 0.0204 mg/L, but after adding Moringa seed adsorbent, the Pb concentration dropped to <0.002mg/L, this means that Moringa seeds are very good at absorbing Pb metal. Hulled Moringa seeds tend to absorb more easily than whole Moringa seeds. The longer the adsorbent takes to adsorb, the Pb concentration decreases until the Pb concentration remains relatively constant.Keywords: Adsorption; Absorbent, Moringa Seeds,Metal